Allergenicity of partially hydrolyzed whey and casein formulas evaluated by ImmunoCAP inhibition assay and basophil activation test - Matsubara, Takeshi; Ishikawa, Fuka; Inuo, Chisato; Fujita, Mayumi; Tsukahara, Ayumi; Koyama, Takahiro; Iwamoto, Hiroshi; Miyaji, Kazuhiro (Frontiers in Allergy, 2023)
Background When exclusive breastfeeding is not possible, partially hydrolyzed formula (PHF) is often used as a starter formula for infants. Some children develop allergic symptoms, including anaphylaxis, after the first intake of cow protein. Therefore, the tolerability of PHF in infants with cow's milk allergy (CMA) is important information. Partially hydrolyzed whey formula (PHWF) is well characterized, but those containing both whey and casein are also available. We evaluated the characteristics of two whey and casein PHFs, PHF1 and PHF2, in vitro and ex vivo, and compared them with a PHWF, PHWF1. Methods Residual antigenicity of β-lactoglobulin (β-LG) and casein in the formulas was measured using ELISA. The molecular weight profile was determined using high-pressure liquid chromatography. IgE reactivity and allergenic activity of the formulas were evaluated by ImmunoCAP inhibition assay and by basophil activation test using blood from patients with CMA, respectively. Results All the participants (n = 10) had casein-specific IgE. The antigenicity of β-LG in PHF1 was similar to that in PHWF1, but it was slightly higher than that in PHWF1 for casein. PHF1 had a higher IgE reactivity than PHWF1. However, PHF1 and PHWF1 had a similar ability to activate basophils. PHF2 had lower antigenicity of casein and β-LG, IgE reactivity and basophil activation than PHWF1. Conclusion These results suggest that the tolerability of PHF1 and PHF2 in patients with CMA is similar to and higher than that of PHWF1, respectively, and that the degree of IgE binding to PHFs does not necessarily correspond to basophil activation.